2015
DOI: 10.1002/anie.201507839
|View full text |Cite
|
Sign up to set email alerts
|

Ceria–Zirconia Particles Wrapped in a 2D Carbon Envelope: Improved Low‐Temperature Oxygen Transfer and Oxidation Activity

Abstract: Engineering the interface between different components of heterogeneous catalysts at nanometer level can radically alter their performances. This is particularly true for ceria-based catalysts where the interactions are critical for obtaining materials with enhanced properties. Here we show that mechanical contact achieved by high-energy milling of CeO2–ZrO2 powders and carbon soot results in the formation of a core of oxide particles wrapped in a thin carbon envelope. This 2D nanoscale carbon arrangement grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 23 publications
5
45
0
3
Order By: Relevance
“…However,m echanochemical activation has not only been used to prepare catalytic materials with properties that match those of heterogeneous catalysts made by conventional methods (e.g.s ol-gel method, co-precipitation, wetness impregnation, etc. ): [25] In numerous cases,b all milling has proven fundamental in designing and improving the interface of solid catalysts, [26] boosting their catalytic and redox behavior, [27] increasing their dispersion on the catalyst matrix surface, [28] enriching the mesoporosity of the solid material, [29] and tempering the thermal conditions required for the heterogeneous catalyst to perform. [26] Although the large majority of the catalysts synthesized by mechanochemistry have been tested in experiments with controlled microreactors,s uch as fixed-bed catalytic reactors, [24] there have been reports where the catalytic activity of the solid materials for reactions at the interface of solid-gas systems was assessed under the application of am echanical force.B elow,w ew ill discuss some of these recent examples,a lthough this is not acomprehensive list.…”
Section: Mechanosynthesis and Use Of Heterogeneous Catalysts With Balmentioning
confidence: 99%
“…However,m echanochemical activation has not only been used to prepare catalytic materials with properties that match those of heterogeneous catalysts made by conventional methods (e.g.s ol-gel method, co-precipitation, wetness impregnation, etc. ): [25] In numerous cases,b all milling has proven fundamental in designing and improving the interface of solid catalysts, [26] boosting their catalytic and redox behavior, [27] increasing their dispersion on the catalyst matrix surface, [28] enriching the mesoporosity of the solid material, [29] and tempering the thermal conditions required for the heterogeneous catalyst to perform. [26] Although the large majority of the catalysts synthesized by mechanochemistry have been tested in experiments with controlled microreactors,s uch as fixed-bed catalytic reactors, [24] there have been reports where the catalytic activity of the solid materials for reactions at the interface of solid-gas systems was assessed under the application of am echanical force.B elow,w ew ill discuss some of these recent examples,a lthough this is not acomprehensive list.…”
Section: Mechanosynthesis and Use Of Heterogeneous Catalysts With Balmentioning
confidence: 99%
“…Theinformation gathered from HRTEM and XPS studies show that on PdCeM there is aunique arrangement of Pd and ceria that is not observed on samples prepared by conventional routes.T his arrangement is the result of an interaction between Pd and ceria promoted by mechanical milling and by the redox characteristics of the two components.W erecently reported that the milling of ceria with carbon soot results in the formation of aCeO 2 core wrapped in asoft carbon shell; [7] the nanoscale arrangement created by mixing was promoted by the different hardness of the two materials that helps the spreading of the softer carbon particles on the surface of ceria. This might explain why the core-shell structure observed here is obtained only when mixing Pd metal nanoparticles and ceria and not when harder materials like PdO and/or ZrO 2 are used (0.6 vs.4GPa for Pd metal and ceria, respectively, against 8f or zirconia [16] ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[3] It is reported from experimental [3b, 4] and computational [5] studies that an enhanced Pd-ceria interaction can improve significantly the catalytic activity of these materials.Inparticular,the presence of Pd into the ceria lattice can lead to the formation of highly reactive Pd 2+/4+ sites that show lower methane activation barriers compared to isolated PdO x units.I nterestingly, differently from what happens on PdO x clusters,o nt hese ionic Pd species methane activation proceeds via hydrogen abstraction, ar oute that is potentially very important for methane utilization. [7] By combining the above mentioned approaches,w eu se ac ontrolled one-step dry milling procedure where Pd metal nanoparticles are put in contact with ceria particles to prepare am ethane oxidation catalyst that outperforms traditional Pd/CeO 2 owing to the unique structural arrangements that characterize metal/support interface at nanoscale.Furthermore,avoiding the use of Pd nitrate or chloride solution significantly reduces waste generation ensuring lower environmental impact. [6] More recently we also investigated the milling of CeO 2 -based materials with carbon, originating a2 Dc arbon layer, covering the ceria particles,a nd improving the interfacial redox exchange between the two materials.…”
mentioning
confidence: 99%
“…[24] Die meisten dieser festen Materialien wurden effektiv in der heterogenen Katalyse gasfçrmiger Substrate angewendet (wie z. [29,26] Obwohl die Mehrheit der mechanisch synthetisierten Katalysatoren in Experimenten mit kontrollierten Mikroreaktoren, wie Festbettreaktoren, [24] getestet wurden, gibt es Berichte,indenen die katalytische Aktivitätder festen Materialien unter Anwendung mechanischer Energie in Reaktionen an der Grenzfläche von Festkçrper-Gas-Systemen bewertet wurde.I mF olgenden werden wir einige dieser jüngsten Beispiele diskutieren, wobei die Liste nicht vollständig ist. Die mechanochemische Aktivierung wurde jedoch nicht nur zur Herstellung von katalytischen Materialien mit Eigenschaften, die denen von durch konventionelle Methoden (z.…”
Section: Mechanochemische Reaktionen Durch Kugelmahlenunclassified
“…hergestellten heterogenen Katalysatoren entsprechen, eingesetzt. [25] In vielen Fällen erwies sich Kugelmahlen als essentiell füre ine Verbesserung der Oberfläche eines festen Katalysators, [26] der Optimierung des katalytischen und des Redoxverhaltens, [27] der Erhçhung der Dispersion auf der Katalysatormatrixoberfläche, [28] die Steigerung der Mesoporositätd es Festkçrpers und die Milderung der thermischen Bedingungen, die der heterogene Katalysator zur Funktion bençtigt. [29,26] Obwohl die Mehrheit der mechanisch synthetisierten Katalysatoren in Experimenten mit kontrollierten Mikroreaktoren, wie Festbettreaktoren, [24] [31] Im Jahr 2011 verçffentlichten Mulas et al eine mechanochemische Hydrierung von Kohlenmonoxid an mechanochemisch dargestellten heterogenen Katalysatoren [Gl.…”
Section: Mechanochemische Reaktionen Durch Kugelmahlenunclassified